Clinical estimation of α/β values for prostate cancer from isoeffective phase III randomized trials with moderately hypofractionated radiotherapy. (3rd July 2018) - Datta, Niloy R.; Stutz, Emanuel; Rogers, Susanne; Bodis, Stephan
Abstract: Background: The α/β values for prostate cancer (PCa) are usually assumed to be low (1.0–1.8 Gy). This study estimated the α/β values of PCa from phase III randomized trials of conventional (CRT) versus hypofractionated (HRT) external beam radiotherapy (RT), reported as isoeffective in terms of their 5-year biochemical (BF) or biochemical and/or clinical failure (BCF) rates. Material and methods: The α/β for each trial was estimated from the equivalent biological effective doses using the linear-quadratic model for each of their HRT and CRT schedules. The cumulative outcomes of these trials were evaluated by meta-analysis for odds ratio (OR), risk ratio (RR) and risk difference (RD). Results: Eight trials from seven studies, randomized 6993 patients between CRT ( n = 2941) and HRT ( n = 4052). RT treatment varied between the two treatment groups in terms of dose/fraction, total dose, overall treatment time and %patients on androgen deprivation therapy (ADT). Differences in OR, RR, and RD for both BF and BCF were nonsignificant. The computed α/β ranged from 1.3 to 11.1 Gy (4.9 ± 3.9 Gy; 95% CI: 1.6–8.2). On multivariate regression, %ADT was the sole determinant of computed α/β (model R 2 : 0.98, p < .001). Conclusions: Clinically estimated α/β for PCa from isoeffective randomized trials using known variables in the linear-quadratic expression ranged between 1.3 and 11.1 Gy. The estimated α/β values were inversely related to %ADT usage, which should be considered when planning future RT dose-fractionation schedules.